COVID-19 Lockdown & Online Education: Impact of WorldWide Pandemic on Nursing Education in India - Manisha Praharaj; Kshirabdhi Tanaya (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background : The technology has taken over all most all aspects of our life including our education system.The present pandemic COVID 19 has affected the education of nursing students. So many institutions haveadopted online teaching so that students can learn and improve their self-confidence.Objectives: The aim of this study is to assess the nursing student’s attitude towards online education andfactors affecting online education.Methods: A total of 780 participants from different nursing institutions of Odisha completed a questionnairebased survey on the impact of pandemic on education of nursing students. A self-structured questionnairewas used to collect data. Participants were selected by convenient sampling method. The demographiccharacteristics were represented by frequencies and percentage. Descriptive statistics for all categoriescalculated based on the responses.Results: Among the participants (n=780), all most all participants 87.9% were females, most participants79.4% of participants were between 18 to 28 years. Among all participants 56.8% are doing Basic Bsc.nursing, 10.1% are continuing Msc Nursing, 29% are in GNM course, and 4.1% are continuing post basicnursing. Maximum of 48.8% are in 1st year. All most all 98.5% of institution conducting online education.39.3% of students have positive attitude and 28.4% of students have negative attitude towards onlineteaching. 72% students have poor internet connection, 52% students have lack of knowledge regardingusing the software, 67% students feel audio was not clear, 56% students feel letters are small to read, 47%participants feel time is not sufficient, 68% participants feel there was interruption during class.Conclusion: The online education has not developed overnight. This system of education adopted by manyhigher educations and in many institutions. Online teaching